Canning & preserving for dummies ebook - Jeanroy, Amelia (2021)
Get your food preservation skills in the can Craving a juicy peach in the barren midwinter? Yearning for a cupful of home-grown tomato soup before the seeds are even in the ground? Canning makes you the ultimate boss of your food supply all year 'round and helps you reduce costs and maintain quality control over what you eat—and to be prepared in times of food shortages. And Canning & Preserving For Dummies shows you how to do it all, helping you explore hundreds-of-years-old traditions of food preservation in the comfort of your own home. In a friendly and step-by-step style, longtime canner and owner of TheFarmingWife.com Amy Jeanroy takes you inside the canning world to show how modern technology and techniques have made it easy to use the four main methods of preservation—water-bath and pressure canning, freezing, and dehydrating—to keep your pantry packed with delicious, out-of-season delights. She also clues you in on how to match preservation technique to food for the most flavorful results—and what supplies to keep on hand for your next canning adventure. Know the benefits, from healthier eating to self-reliance Follow the latest food safety guidelines Get guidance on food storage in urban living Cook up tasty recipes with your preserved delights Whatever draws you to canning—saving money on groceries, healthy living, or the sheer fun of doing it—this book is stuffed with all the goodness you need to keep your palate happy whatever the season is!